ШЕВЧЕНКОВА КОНЦЕПЦІЯ УКРАЇНИ НА ТЛІ ВИКЛИКІВ НАЦІОНАЛЬНОГО БУТТЯ ДОБИ - Гудима, Анна (Taras Shevchenko National University of Kyiv (Ukraine), 2023)
У розвідці розглядається концепція України Т. Шевченка у двох аспектах: як верховної цінності та втілення національної ідеї – в контексті національного буття доби та викликів, які стояли перед українством. Головним із них була загроза перетворення на малоросів. На кінець XVIII ст. імперії фактично вдалося поглинути Україну та позбавити українців свого самоствердження через політику денаціоналізації та русифікації. Ефективним засобом денаціоналізації, впроваджуваної імперією щодо українців, було позбавлення їх свого імені, адже серед атрибутів нації саме назва є первинним. У літературі першої половини ХІХ ст. (до Т. Шевченка), ознаменованої потужним національним рухом, не було протистояння росії (у розвідці найменування "росія", "російська імперія" принципово вживаємо з малої літери. – А. Г.). Тогочасна українська інтелігенція засвоїла концепт домінування росії над Україною. Ведучи мову про поетову концепцію України, ми звернули увагу на відмінність бачення України, зведеної до фольклору та минувшини, у добі та Т. Шевченком. Імперському наративу щодо колоніального становища України він протиставляє спершу поезію про козацьку звитягу і визвольні змагання, показує реальний стан занепаду підімперської України, потому розвінчує центральний міф, витворений імперською ідеологією, що істотно впливав на свідомість українців, начебто їхньої єдності з москалями – через особу Б. Хмельницького та, відповідно, подію Переяславської ради (вперше в "Розритій могилі"), а невдовзі пише безжальну антиколонізаторську, антицаристську лірику ("Сон (комедія)", "Кавказ" та ін). Цим Т. Шевченко здійснює переворот в українській суспільній думці, випереджаючи свій час. Т. Шевченко надав темі України нових смислів. Його поезія давала відповіді на найважливіші виклики національного буття: брала участь у творенні національного буття за допомогою слова, відкривала автентичне Я українців, формувала націю як духовну спільноту, протистояла імперській культурі. Т. Шевченко утверджував саму ідею України як самостійного суб'єкта і підносив її до рівня верховної цінності. Доля рідної України, як показує Т. Шевченко, неспівмірно переважає у парадигмі всіх можливих інтересів.

The research examines T. Shevchenko's concept of Ukraine in two aspects: as a supreme value and the embodiment of the national idea – in the context of the national existence of his period and the challenges that faced Ukrainianism. The main one of them was the threat of transformation into an integral part of the Russian nation (inferior part) – the Malorussians. At the end of the 18th century the empire actually managed to absorb Ukraine and deprive Ukrainians of their self-assertion, through the policy of denationalization and Russification. Depriving Ukrainians of their name was an effective means of denationalization implemented by the empire, because among the attributes of the nation, the name itself is primary. The literature of the first half of the 19th century (prior to T. Shevchenko), marked by a powerful national movement, had no manifestations of opposition to Russia. The Ukrainian intelligentsia of that time mastered the concept of Russia's dominance over Ukraine. While talking about the poetic concept of Ukraine, we drew attention to the difference between the vision of Ukraine, reduced to folklore and the past events of that period, and the vision of T. Shevchenko. He contrasts the imperial narrative about the colonial situation of Ukraine with the poetry about the Cossack victory and the liberation struggle. T. Shevchenko shows the real state of the decline of the empire-ruled Ukraine. He debunks the central myth created by the imperial ideology, which significantly influenced the consciousness of Ukrainians. This myth states that the unity with Muscovites has been achieved through the person of B. Khmelnytskyi and, accordingly, in the subtext, via the event of the Pereyaslav Agreement. For the first time such thoughts of T. Shevchenko were set out in "The Unearthed Grave"and a little bit later in his merciless anti-colonialist, anti-tsarist lyrics "Night Dream (Сomedy)", "Caucasus", etc.). By doing so, T. Shevchenko makes a revolution in Ukrainian public opinion, being ahead of his time. T. Shevchenko gave new meanings to the topic of Ukraine. His poetry gave answers to the most important challenges of national existence: it participated in the ormation of national existence with the help of words; discovered the authentic self-identity of Ukrainians' formed the nation as a spiritual community; opposed the imperial culture. T. Shevchenko affirmed the very idea of Ukraine as an independent subject. He raised the idea of Ukraine to the level of supreme value. The fate of native Ukraine, as T. Shevchenko shows, disproportionately prevails in the paradigm of all possible interests.
SHEVCHENKO'S CONCEPT OF UKRAINE AGAINST THE BACKGROUND OF THE CHALLENGES OF THE NATIONAL EXISTENCE OF HIS PERIOD
Keywords: T. Shevchenko's poetry; Ukraine; national identity; national existence; malorosiystvo; imperial culture; поезія Т. Шевченка; Україна; національна ідентичність; національне буття; малоросійство; імперська культура